Why was the Color Violet rarely used by Artists before the 1860s? - Tager, Allen (Journal of cognition and culture, 2018)
Although the color violet is now used in a wide variety of everyday products, ranging from toys to clothing to cars, and although it now appears commonly in artistic works, violet was rarely used in fine art before the early 1860s. The color violet only became an integral part of modern culture and life with the rise of the French Impressionists. I investigated the use of violet in over 130,000 artworks prior to 1863 and found that it appeared in about .06 percent of the paintings. Violet was used substantially more frequently in Impressionist works, and remains popular in fine art and in popular culture today. I examine several explanations for the explosion of the use of violet in the art world during the Impressionist era, and conclude that a cognitive-perceptual explanation, based on the heightened sensitivity of the Impressionists to short wavelengths, may account for it. The findings fit with a new understanding about evolutionary changes in planetary light and human adaptation to light.